Influence of stages of economic development on women entrepreneurs’ startups - Dianne H.B. Welsh (2018)
© 2016 Elsevier Inc. Women entrepreneurs add to the economic well-being of countries. This study examines whether stages of economic development (SEDs) influence women entrepreneurs similarly across national settings. This study approaches the environments in which women entrepreneurs launch their businesses from two perspectives – family support and personal problems – in Canada, China, Egypt, Morocco, Poland, South Korea, and Turkey. Findings show that the relationship between SEDs and family instrumental support (financial and organizational) presents an S shape, whereas that between SEDs and family moral support is an inverted S shape. Evidence confirms that the relationship between SEDs and personal problems follows an inverted U-shape, with personal problems increasing with SEDs to an optimal point, above or below which personal problems decrease. This study exemplifies the need for joined theory and practice to influence public policy worldwide. The results are useful for further developing policies to promote women-owned business startups by understanding what barriers women entrepreneurs face and what solutions work best with the stage of country development.